Global Market Expansion And Strategies In Wireless Telecommunication Sector-Case Study Of Mobile Telephone Network (MTN) Group In (WECA) And (MENA) Regions - Mohammed Munssour, Mubarak (2008)
This case study gives an overview of the wireless telecommunication industry, specifically in the West and Central Africa (WECA) and Middle East and Africa (MENA) regions and the analysis of MTN which operates in both regions. The study sheds light on developments in the telecommunications industry in general and specifically on wireless telecommunications sector.